2014
DOI: 10.1186/preaccept-7648644691342004
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting and engineering of the TetR family regulator SACE_7301 for enhanced erythromycin production in Saccharopolyspora erythraea

Abstract: Background: Saccharopolyspora erythraea was extensively utilized for the industrial-scale production of erythromycin A (Er-A), a macrolide antibiotic commonly used in human medicine. Yet, S. erythraea lacks regulatory genes in the erythromycin biosynthetic gene (ery) cluster, hampering efforts to enhance Er-A production via the engineering of regulatory genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We previously identified and dissected the two TFRs, SACE_3986 and SACE_7301, involved in the erythromycin production, and SACE_3986 inactivation or SACE_7301 overexpression in the industrial S. erythraea WB resulted in the yield improvement. 24 , 25 Herein, we examined their interaction relationship to SACE_3446 via qRT-PCR and EMSA analysis. Compared with wild-type A226, Δ SACE_3446 did not exhibit differential expression of SACE_7301 and SACE_3986 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously identified and dissected the two TFRs, SACE_3986 and SACE_7301, involved in the erythromycin production, and SACE_3986 inactivation or SACE_7301 overexpression in the industrial S. erythraea WB resulted in the yield improvement. 24 , 25 Herein, we examined their interaction relationship to SACE_3446 via qRT-PCR and EMSA analysis. Compared with wild-type A226, Δ SACE_3446 did not exhibit differential expression of SACE_7301 and SACE_3986 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a ). A previous study demonstrated that overexpression of SACE_7301 in WB dramatically elevated its erythromycin A yield, 25 thereby we expressed SACE_7301 with 3 extra copies under the control of P ermE * in the WBΔ 3446 Δ 3986 , to yield WBΔ 3446 – 3986 /3 × 7301 . Interestingly, erythromycin A yield in WBΔ 3446 – 3986 /3 × 7301 was dramatically decreased relative to that in WBΔ 3446 – 3986 , but a little higher than that in WB ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations